Analisis Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Mega Cipta Logistik - Yayan Yanuari; Romadhon (Mulia Pratama, 2023)
The companies, both large and small, get profits, to realize this the company requires financial management. This research basically discusses the analysis of the influence of sales, operating costs and operating profit on PT. Gudang Garam TBK. This study aims to determine the profit generated based on sales and operating costs incurred at PT. Gudang Garam TBK. Sales is an interaction between individuals who meet face to face aimed at creating, improving, controlling or maintaining an exchange relationship so that it is profitable for the other party. Operating expenses are all costs related to operations outside the production process, including (1) selling costs and (2) general and administrative costs”. operating profit is as follows: ”Operating profit comes from transactions between revenues, expenses, gains and losses. Profit is obtained from income minus costs over a certain period of time. for 4 years starting from 2018 to 2021. The sample in this study is the income statement, namely sales, operating costs and operating profit in obtaining the author's data using data on the IDX which can be accessed through www.idx.co.id. The types of data used are primary data and secondary data. The data analysis method used is descriptive analysis method. In conclusion, Sales in 2019 amounted to Rp. 110,523,819 from 2018 the increase increased by 0.1548 to 15.5%. Operational costs in 2019 amounted to Rp. 7,993,256, from 2018 the increase increased by 0.058 to 5.58%. In 2019 operating profit From 2018 it increased by 0.351 to 35.1%. In 2020 sales of Rp. 114,477.311 from 2019 An increase of 0.0357 to 3.6%. In 2020 the operational cost is Rp. 7,581,497, from 2019 Decrease in operating costs by - 0.0515 to - 5.15%. So that the operating profit obtained in 2020 is Rp. 10,045,855 from 2019 operating profit decreased by - 0.333 to - 33.3%. In 2021, sales of Rp. 124,881,266 from 2020, an increase of 0.0908 to 9.08%. In 2021 the operational cost is Rp. 7,159.938 from 2020 decreased by 0.0556 to 5.56%. In 2021 operating profit experienced a very drastic decrease from 2020, namely a decrease of -0.2671 to -26.71%. This is due to a fairly high increase in customs duties. The population used in this study is the financial statements of PT. Gudang Garam TBK. Based on the research results, it is known that the sales and operational costs of PT. Gudang Garam TBK. in 2019-2021 will affect operating profit.